W jaki sposób należało opiekować się dzieckiem w pierwszych tygodniach jego życia? Zalecenia autorów wybranych średniowiecznych (XI-XV) traktatów medycznych - Anna Głusiuk (Saeculum Christianum)
The article discusses issues related to childcare in the first weeks of the baby’s life using selected medieval medical treatises as examples. Based on Liber de sinthomatibusmulierumand De curis mulierum attributed to Trotula of Salerno, who lived in the 11th/12th centuries, Ad mulieres ferrarienses de regimine pregnantium et noviter natorum usque ad septenniumby Michael Savonarola and Régime du corps by Aldobrandin of Siena, it is presented how, according to medical knowledge of the time, babies should be cared for in their first weeks of life. The authors discussed a.o., how to cut the umbilical cord correctly, bathe the baby or, if necessary, choose a suitable wet nurse who would breastfeed the child instead of a mother.